Musica umana, ascolto postumano - Viel, Massimiliano (Scenari, 2021)
The constant presence of the extramusical in the history of Western music seems to support the idea of posthuman in music. The assimilation of the extramusical to the musical, necessary to the composition of music, is not however able to found a posthuman thought. We then ask ourselves about the state of necessity of music in the diversity of human cultures, concluding that it is precisely the idea of music itself, an idea of European origin, that is the bearer of humanist thought. It concludes with a perspective on listening as a possible tool for opening up to the posthuman, as exemplified by the practice of soundwalk.